Transparency in Organizing: A Performative Approach - Oana Brindusa Albu (Copenhagen Business School (CBS), 2014)
This dissertation provides a critical analysis of transparency in the context of organizing. The empirical material is based on qualitative studies of international cooperative organizations. The dissertation seeks to contribute to transparency and organizing scholarship by adopting a communication centred approach to explore the implications of pursuing ideals of transparency in organizational relationships. The dissertation is comprised of four papers each contributing to extant debates in organizational studies and transparency literature. The findings indicate that transparency, in contrast to being a solution for efficiency and democratic organizing, is a communicatively contested process which may lead to unintended consequences. The dissertation shows that transparency is performative: it can impact authority by de/legitimating action, shape the processes of organizational identity co-construction, and its intersection with new media technologies can create tensions. Thus, the dissertation questions instrumental tendencies which regard transparency as full disclosure, the opposite of secrecy, and a way to achieve a consistent organizational identity. The dissertation provides a framework of organizational transparency which underlines its negotiated, power-infused and paradoxical nature.
hdl:10398/8916
Keywords: 650